LINGUISTIC INTERPRETATION OF THE DERIVATION IN THE GERMAN LANGUAGE - Aburakhmanov Sirojiddin Muminkulovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The field of derivation has an independent status today as a separate branch of linguistics. Since it is specific to the study of derivation problems, it is inextricably linked with this concept from the etymological point of view. It is known that before using a term, it is necessary to explain its essence and meaning. Therefore, let's first pay attention to the lexical meaning of the word derivation. This word is actually derived from the Latin word, derivation-, which means that one thing is separated from another. In other words, derivation means that one element branches off from another element. It can be seen that among the above meanings of the word "derivation", only the concept of "word formation" is of grammatical importance. That is why the term "derivation" has been used only in the lexical plan, that is, in the context of word formation, until the current stage of linguistics. The concept of "lexical derivation" has just started to be used as a linguistic term, as mentioned above. The term "derivatology" was adopted in 1981 at the prestigious scientific conference held at Perm University on the topic "Theoretical problems of derivatology". It can be seen that among the above meanings of the word "derivation", only the concept of "word formation" is of grammatical importance. That is why the term "derivation" has been used only in the lexical plan, that is, in the context of word formation, until the current stage of linguistics. The concept of "lexical derivation" has just started to be used as a linguistic term, as mentioned above. The term "derivatology" was adopted in 1981 at the prestigious scientific conference held at Perm University on the topic "Theoretical problems of derivatology".